Effect of rapid rehabilitation surgery on postoperative rehabilitation, complications and long-term prognosis in radical laryngectomy: a PSM matching study - Huang, Yibo; Wang, Meifang; Pu, Jianfeng; Zang, Yunpeng; He, Teng (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the effects of Enhanced Recovery After Surgery (ERAS) on postoperative rehabilitation, complications, and long-term prognosis in patients undergoing radical laryngectomy using a single-center propensity score matching (PSM) study.MethodsA retrospective cohort study included patients newly diagnosed with laryngeal cancer between January 1, 2019, and January 1, 2021, scheduled for partial laryngectomy. The control group (CG) comprised patients treated with standard interventions in 2019, while the research group (RG) included patients undergoing ERAS in 2020. After exclusions, 233 individuals remained: 94 in the RG and 204 in the CG. Following PSM in a 2:1 ratio, there were 180 in the CG and 90 in the RG. Relevant indices were analyzed.ResultsNo significant differences were found in baseline characteristics (p > 0.05). The RG showed significantly lower hospital stay, nasogastric tube and tracheal cannula duration, early enteral nutrition, hospitalization expenses, and readmission rates compared to the CG (p < 0.05). The RG had higher albumin and prealbumin levels on postoperative days 3 and 7 (p < 0.05) but not on day 1 (p > 0.05). No significant differences were found in 1-year or 2-year overall survival rates, nor in recurrence-free survival rates between the groups (p > 0.05), though the RG showed marginally better survival.ConclusionERAS treatment for postoperative laryngeal cancer patients reduces hospitalization duration, nasogastric tube and tracheal cannula use, costs, readmission rates, and complications, while accelerating recovery and facilitating early discharge. ERAS enhances patient comfort and clinical outcomes, supporting broader clinical adoption.